The Evaluation of Zoomed Echo-Planar Diffusion-Weighted Magnetic Resonance Imaging With Two-dimensional Spatial-Selective Radiofrequency Excitation Pulses in Patients With Hilar Cholangiocarcinoma - Liu, Jingjing; Huang, Mengyue; Ren, Yanan; Xu, Man; Li, Yinhua; Cheng, Jingliang; Zhu, Jinxia (Frontiers in Oncology, 2022)
Background: We aimed to investigate the feasibility of using the zoomed diffusion-weighted echo-planar imaging (z-EPI DWI) sequences for hilar cholangiocarcinoma assessment compared with conventional single-shot EPI diffusion-weighted imaging (c-EPI DWI). In addition, the resultant image quality was assessed. Methods: Both c-EPI DWI and z-EPI DWI were preoperatively performed in 16 patients with histopathologically-confirmed hilar cholangiocarcinoma. A two-dimensional spatial-selective radiofrequency (RF) pulse was applied to the z-EPI DWI using an echo-planar transmit trajectory. Anatomic structural visualization, lesion conspicuity, artifact presence and overall image quality were evaluated and compared between the two sequence images. The ratio of differences regarding hilar cholangiocarcinoma lesion sizes was measured on T2-weighted imaging (T2WI) and diffusion-weighted imaging (DWI) were acquired from both EPI techniques. The DW images for tumor involvement of the bile duct were reviewed based on histopathological examination of the surgical intraoperative evaluation. Results: The hepatic hilar region was delineated by visualization of anatomical structures, lesion conspicuity and overall image quality using the z-EPI DWI and this analysis was compared with the c-EPI DWI method (all p<0.05). Better lesion delineation of bile duct walls and lumens was noted in four patients with z-EPI DWI compared with those of c-EPI. No significant differences were noted between the two image datasets for artifacts (p=0.876). The ratio of differences regarding hilar cholangiocarcinoma lesion sizes was significantly lower (p= 0.018) on T2WI and DWI, as determined by the z-EPI DWI than that determined by the c-EPI method. The use of z-EPI DWI resulted in the accurate diagnosis of the Bismuth-Corlette classification of 15 tumors (15/16, 93.75%) for both of the two observers, whereas the use of c-EPI DWI resulted in correct diagnosis of 12 tumors (12/16, 75.00%). Conclusion: z-EPI DWI resulted in remarkable image quality improvements for hilar cholangiocarcinoma. The ability to detect and delineate lesions using z-EPI DWI was superior to that of c-EPI.